Efficacy, Retention Rate, and Influencing Factors of Ketogenic Diet Therapy in Children with Refractory Epilepsy: A Retrospective Study - Shen, Jue; Jiang, Tiejia; Gao, Feng; Jiang, Kewen (Neuropediatrics, 2022)
Background This study aimed to evaluate the efficacy and retention rate of a ketogenic diet (KD) and assess factors that influence the efficacy of KD therapy in children with refractory epilepsy (RE).Methods We retrospectively studied the efficacy and retention rate of 56 RE children who accepted KD therapy from January 2013 to December 2019. Patients who had a ≥50% reduction in seizure frequency were defined as responders. The retention rate was calculated as the proportion of children who continued KD/the total number of children who were followed up at the time of enrollment. We also analyzed the effects of different factors (such as gender, KD initial age, KD duration, the type of epilepsy syndrome, and others) on the efficacy of the KD.Results (1) The efficacy rates for the KD at 3, 6, 12, and 18 months were 51.8, 53.6, 39.2, and 23.2%, respectively. (2) The retention rates for the KD at 3, 6, 12 and 18 months were 100, 69.6, 41.1, and 23.2%, respectively. (3) There was no correlation between efficacy and gender, epilepsy onset age, the type of epilepsy syndrome, electroencephalogram improvement, or the number of antiseizure medications, while cranial magnetic resonance imaging (MRI) abnormalities, KD duration, and KD initial age affected its efficacy at 3 months.Conclusion (1) KD therapy for refractory childhood epilepsy was effective and produced a high retention rate. (2) MRI abnormalities and the initial age and duration of KD influenced its short-term efficacy in RE children.
Keywords: ketogenic diet; refractory epilepsy; efficacy; retention rate; influencing factors